To study the criteria intelligent building and building automation system in Malaysia focusing office building in Perak / Mohammed Tasnim Rosly Mohammed - Rosly Mohammed, Mohammed Tasnim (2021)
Nowadays, the world has faced a crisis to maintain a comfortable environment. Therefore, it is the duty and our responsibility to protect our environment in everything we can for our own benefits and also for future generations. One way to save the environment is to save energy in the buildings. The definition of Intelligent Building can be classified by systematic control information and services that meet the needs and expectations of occupants. Therefore, IBAS is very important in the building which have advantages to produce the best comfortable and safety in the building environment. The aim is to determine the criteria Intelligent Building and Building Automation System. Intelligent building is a new technology and business process management in the present dire need for intelligent buildings. So, questionnaire has been distributed in completing this study. Three case studies have been selected, that is MBI, PTTC and KWSP in Ipoh, Perak. The data was proceeding by SPSS software and variable frequency. This study will reach to determine the criteria Intelligent Building and Building Automation System.